ENVIRONMENTAL POLLUTION AND ITS INFLUENCE ON HUMAN HEALTH IN THE IRAQI ENVIRONMENT - Maysaa Younis Ali (Scholar Express Journals, 2022)
The researcher's purpose in doing this study is to investigate Iraq's environment and the level of pollution in the country It also investigates the negative effects of pollution on human health, such as air, water, soil, food, auditory, and visual pollution, which rapidly affects human health through disease. Understanding Iraq's environmental problems and pollution through investigating the many causes of environmental deterioration in Iraq
Keywords: Environmental Survey; Its Negative Consequences; Pollutant Type